KEMUNGKINAN PENGGUNAAN NANO KARBON DARI LIGNOSELULOSA SEBAGAI BIOSENSOR - Gustan Pari; Adi Santoso; Djeni Hendra; Buchari; Akhirudin Maddu; Mamat Rachmat; Muji Harsini; Bunga Ayu Safitri; Teddi Heriyanto; Saptadi Darmawan (BRIN Publishing, 2016)
In the forest products field, the nano technology that can be developed is among others nano carbon derived from lignocellulosic stuffs. In relevant, this paper observes information and technology on the charcoal processing from lignocellulosic stuffs into nano carbon. The lignocellulosic stuffs used in this research consisted of teak wood, further carbonized into charcoal at 400-500 C using drum kiln and then purified by re-carbonizing it at 800 C for 60 minutes by using steam and sodium hydroxide (KOH) 15% as activation agent. Prior to purification, the charcoal sustained the doping (intercalation) process with Nicel and re-carbonize again at 900 C for 60 minutes. The qualities and structure of all the resulting carbon were evaluated using nano scale device pyrolysis-gas chromatography mass spectrophotomtry (PyGCMS), scanning electron microscope-energy disverse spectrophotometry (SEM-EDS and X-ray diffraction (XRD), and examined as well of their dielectric characteristics. Result show charcoal was examined of its physical and chemical properties. Manufacture of biosensor by using molecularly imprinted polimer (MIP) system based on carbon paste and optimizing. Results show that nano carbon from lignocellulose can be made for biosensor with MIP system. Optimized formulation were mixed with15% MIP, 45% carbon and 40% parafine with nernst factor of 49 mV/decade and limit detection of 1.02x10-6 M at pH4.